Effect of KOH Activator on the Performance of Activated Carbon from Oil Palm Kernel Shell as Supercapacitor Electrode Material - Yola Azli Perdana; Rahma Joni; Emriadi Emriadi; Hemansyah Aziz (Journal of Aceh Physics Society, 2020)
Karbon aktif dari cangkang kelapa sawit sebagai bahan elektroda superkapasitor telah diteliti. Superkapasitor dirangkai dengan metoda plat/sandwich yang dipisahkan oleh separator. Untuk mendapatkan nilai kapasitansi yang besar dilakukan variasi jumlah aktivator terhadap karbon menggunakan aktivator KOH. Sifat fisikokimia dari karbon aktif diteliti dengan melakukan karakterisasi menggunakan XRD (X-Ray Diffraction), SEM-EDX (Scanning Electron Microscopy-Energy Dispersive X-Ray) dan SAA (Surface Area Analyzer) dan sifat elektrokimianya diteliti dengan pengukuran CV (Cyclic Voltammetry). Karbon aktif dengan perbandingan 1:5 memiliki luas permukaan yang paling besar yaitu 793,326 m2/g dan nilai kapasitansi spesifik tertinggi yaitu 99,151 F/g. The activated carbon from oil palm kernel shell as an electrode material for supercapacitors has been investigated. The supercapasitor was assembled by plate/sandwich methods. Both electrodes were separated by using a separator. To increase the capacitancy value, variations in the number of activators on carbon were carried out using KOH activator. The physicochemical properties of activated carbon were investigated by characterizing using XRD (X-Ray Diffraction), SEM-EDX (Scanning Electron Microscopy-Energy Dispersive X-Ray) and SAA (Surface Area Analyzer) and the electrochemical properties were investigated by measuring CV (Cyclic Voltammetry). Activated carbon with a ratio of 1:5 has the largest surface area of 793,326 m2/g and the highest specific capacitance value is 99,151 F/g.Keywords: activated carbon, supercapasitor, activator, surface area, specific capacitance